2011
DOI: 10.5194/acp-11-53-2011
|View full text |Cite
|
Sign up to set email alerts
|

Manchester Ice Nucleus Counter (MINC) measurements from the 2007 International workshop on Comparing Ice nucleation Measuring Systems (ICIS-2007)

Abstract: Abstract. An ice nucleus counter was developed and constructed to enable investigation of potential ice nucleating materials. The Manchester Ice Nucleus Chamber (MINC) is a concentric-cylinder continuous flow diffusion chamber (CFDC). A full explanation of the MINC instrument is given here, along with first results and a comparison to an established instrument of similar design (Colorado State University CFDC) during sampling of common ice nucleating aerosols at the 2007 International workshop on Comparing Ice… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…For example, during the 2007 International Workshop on Comparing Ice Nucleation Measuring Systems (ICIS-2007) in Germany Möhler et al, 2008), instruments encompassing continuous flow diffusion chambers (e.g., the CFDC of CSU), static diffusion chambers, mixing chambers, and expansion chambers were used to investigate different particle types including mineral dust and bacteria (Snomax ® , hereafter Snomax). In general, the fraction of aerosols serving as INPs as a function of temperature and RH between all instruments agreed within a factor of 4-5 (DeMott et al, 20084-5 (DeMott et al, , 20114-5 (DeMott et al, , 2015Jones et al, 2011). Similar differences were observed between the Aerosol Interactions and Dynamics in the Atmosphere (AIDA) cloud expansion chamber (Möhler et al, 2006) and the CFDC of CSU during the Third AerosolCloud Interaction (ACI03) campaign with samples of ambient aerosols and coated and uncoated Asian dust .…”
Section: Moudi-dft and Cfdc Intercomparisonmentioning
confidence: 99%
“…For example, during the 2007 International Workshop on Comparing Ice Nucleation Measuring Systems (ICIS-2007) in Germany Möhler et al, 2008), instruments encompassing continuous flow diffusion chambers (e.g., the CFDC of CSU), static diffusion chambers, mixing chambers, and expansion chambers were used to investigate different particle types including mineral dust and bacteria (Snomax ® , hereafter Snomax). In general, the fraction of aerosols serving as INPs as a function of temperature and RH between all instruments agreed within a factor of 4-5 (DeMott et al, 20084-5 (DeMott et al, , 20114-5 (DeMott et al, , 2015Jones et al, 2011). Similar differences were observed between the Aerosol Interactions and Dynamics in the Atmosphere (AIDA) cloud expansion chamber (Möhler et al, 2006) and the CFDC of CSU during the Third AerosolCloud Interaction (ACI03) campaign with samples of ambient aerosols and coated and uncoated Asian dust .…”
Section: Moudi-dft and Cfdc Intercomparisonmentioning
confidence: 99%
“…Koehler et al (2010) observed ice nucleation at water saturation at highest temperatures of 237-243 K for 200-400 nm particles. An activated fraction of 0.1 % at water saturation at ∼ 251 K was observed by Jones et al (2011) for an aerosol containing ATD particles with diameters < 1 µm. The data point at 256 K is uncertain because it was measured at a supersaturation with respect to water of 5 %.…”
Section: Arizona Test Dust (Atd)mentioning
confidence: 99%
“…5a therefore lie on the water saturation line. Only for Snomax ™ , an artificial snow inducer consisting of freeze-dried Pseudomonas syringae bacteria cells, cell debris and dried culture medium (Lagriffoul et al, 2010), deposition nucleation has been studied extensively (Chernoff and Bertram, 2010;Jones et al, 2011;Kanji et al, 2011;DeMott et al, 2011). More results on freezing experiments with biological particles, also from other habitats, are discussed in Després et al (2012).…”
Section: Primary Biological Aerosol Particlesmentioning
confidence: 99%
“…(1) can also be applied to polydisperse The data by Kanji et al (2008) are interpolated to the same total particle surface areas. The data by Jones et al (2011) are from the CSU-CFDC instrument and for water-subsaturated conditions. particles, with A aer obtained from the total aerosol surface area concentration divided by the total aerosol number concentration.…”
Section: Surface Area Dependencementioning
confidence: 99%